Treatment of Endovascular Coil and Stent Migration Using the Merci Retriever: Report of Three Cases - Kung, David K. (Hindawi Publishing Corporation, 2012)
Background. Coil and stent migration is a potentially catastrophic complication in endovascular neurosurgery, which may lead to cerebral thromboembolism. Techniques for removing migrated coil and stent are not well established. Methods and Results. We present three cases in which coil or stent migration occurred during endovascular embolization of a cerebral aneurysm. The Merci Retrievers were used successfully in all cases to remove the displaced foreign bodies. Technical details are described. Conclusion. The Merci Retriever device can be utilized successfully for removal of migrated coils and stents in endovascular neurosurgery.